Does shrub benefit the thermal comfort at pedestrian height in Singapore?. (December 2021) - Li, Jiayu; Zheng, Bohong; Ouyang, Xiao; Chen, Xiao; Bedra, Komi Bernard
Highlights: Shrubs significantly block the wind speed at pedestrian height No differences are detected in air temperature at pedestrian height with shrubs In Singapore, shrubs do increase relative humidity particularly at noon The PETs at pedestrian height are deteriorated by the shrub in Singapore Abstract: Shrubs have little effect on shading while effectively blocking the wind. Singapore has abundant solar radiation and sea breeze resources where shrubs are not as common as trees or grasses in its built area. This research aims at investigating this phenomenon and clarifying the impacts of shrubs on thermal comfort at pedestrian height. Singapore's buildings and shrubs are reviewed and the Envi-met model is employed for simulation after its accuracy is confirmed by the field experiment. The influence of shrubs on air temperature, wind speed, and relative humidity at the height of 1.5 meters are analysed, then the physiologically equivalent temperature is calculated. The analytical results reveal that, overall, shrub deteriorates the thermal comfort at pedestrian height in Singapore. In fact, shrubs do not have any significant impact on air temperature at the pedestrian level but do reduce wind speed, and slightly increase the relative humidity, which leads to an increase of PET during the daytime. The study argues that not all plants do enhance thermal comfort in our living environment, and the appropriate selection of vegetation types should consider regional or local climate features.